2014
DOI: 10.1007/s00256-014-1951-1
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography for diagnosis of bisphosphonate-related osteonecrosis of the jaw: evaluation of quantitative and qualitative image parameters

Abstract: BRONJ can be effectively diagnosed with CBCT. Qualitative image parameters yield a higher diagnostic performance than quantitative parameters, and ROI-based attenuation measurements were more accurate than VOI-based measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 26 publications
2
35
0
1
Order By: Relevance
“…[7][8][9]11 According to these authors, BRONJ diagnosis based on bone exposure is a late diagnosis, which is responsible for the refractory behaviour of the disease. In the meantime, studies have analyzed imaging modalities such as radiography, helical CT, CBCT, MR and bone scintigraphy, in search of imaging signs to confirm BRONJ, [12][13][14] where persisting alveolar socket, bone sclerosis, osteolysis, thickening of the lamina dura, narrowing of the mandibular canal, widening of the periodontal ligament space and sequestrum have been reported as the most significant ones. 15,16 Although helpful in determining the extension of the lesion, none of these examinations alone is capable of diagnosing BRONJ, without clinical signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9]11 According to these authors, BRONJ diagnosis based on bone exposure is a late diagnosis, which is responsible for the refractory behaviour of the disease. In the meantime, studies have analyzed imaging modalities such as radiography, helical CT, CBCT, MR and bone scintigraphy, in search of imaging signs to confirm BRONJ, [12][13][14] where persisting alveolar socket, bone sclerosis, osteolysis, thickening of the lamina dura, narrowing of the mandibular canal, widening of the periodontal ligament space and sequestrum have been reported as the most significant ones. 15,16 Although helpful in determining the extension of the lesion, none of these examinations alone is capable of diagnosing BRONJ, without clinical signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al (2017) reported that the bone scan index of the jaw was significantly higher in patients who developed ONJ than in those who did not, 3 months before the diagnosis of ONJ, underlining its value as a new prognostic index. More advanced imaging procedures like computed tomography (which can evaluate the radiodensity of necrotic bone) (Hamada, Matsuo, Koizumi, Satomi, & Chikazu, 2014), and cone beam computed tomography, are considered superior to established panoramic radiography, and represent a potential additional tool to assist surgical management of ONJ (Guggenberger et al, 2014;Kammerer et al, 2016). More advanced imaging procedures like computed tomography (which can evaluate the radiodensity of necrotic bone) (Hamada, Matsuo, Koizumi, Satomi, & Chikazu, 2014), and cone beam computed tomography, are considered superior to established panoramic radiography, and represent a potential additional tool to assist surgical management of ONJ (Guggenberger et al, 2014;Kammerer et al, 2016).…”
Section: Predictive and Prognostic Factorsmentioning
confidence: 99%
“…Despite its greater ability to detect bone changes in BRONJ compared with panoramic radiography, CT involves a high cost and high radiation exposure. 48 These disadvantages have been overcome by CBCT, which provides a three-dimensional image, but with lower radiation dose, easier accessibility and lower cost than CT. 44,48,49 The applied radiation dose in CBCT, depending on the equipment used and the area scanned, is between 3 and 20% of a CT scan, but it is still high compared with conventional dental radiography techniques. 49,50 Compared with panoramic radiography, CBCT provides an equivalent patient radiation dose of 5-74 times that of a single film-based panoramic X-ray.…”
Section: Imaging Findingsmentioning
confidence: 99%
“…Also, the time spent for image acquisition is lower than that in CT, where the average time for one CBCT scan may vary from 10 to 30 s. 46 Early BRONJ changes often begin with periosteal thickening prior to evolving into overt sclerotic foci, whereas focal osteolytic changes represent bone degradation specific to advanced stages of osteonecrosis. CBCT may be able to detect early changes, such as periosteal thickening, bone density alterations, 49 loss of trabecular bone and erosion of cortical bone, 51 before the necrotic bone can be detected on clinical examination. Barragan-Adjemian et al 52 described involucrum as a necrotic body formation inside the trabeculae in the sclerotic mandibular bone they analyzed in CBCT of patients under bisphosphonate therapy.…”
Section: Imaging Findingsmentioning
confidence: 99%
See 1 more Smart Citation